Considering Intrauterine Location in a Model of Fetal Growth Restriction After Maternal Titanium Dioxide Nanoparticle Inhalation - D'Errico, J. N.; Fournier, S. B.; Stapleton, P. A. (Frontiers in Toxicology, 2021)
Fetal growth restriction (FGR) is a condition with several underlying etiologies including gestational disease (e.g., preeclampsia, gestational diabetes) and xenobiotic exposure (e.g., environmental contaminants, pharmaceuticals, recreational drugs). Rodent models allow study of FGR pathogenesis. However, given the multiparous rodent pregnancy, fetal growth variability within uterine horns may arise. To ascertain whether intrauterine position is a determinant of fetal growth, we redesigned fetal weight analysis to include litter size and maternal weight. Our FGR model is produced by exposing pregnant Sprague Dawley rats to aerosolized titanium dioxide nanoparticles at 9.44  0.26 mg/m3 on gestational day (GD) 4, GD 12 or GD 17 or 9.53  1.01 mg/m3 between GD 4-GD 19. In this study fetal weight data was reorganized by intrauterine location [i.e., right/left uterine horn and ovarian/middle/vaginal position] and normalized by maternal weight and number of feti per uterine horn. A significant difference in fetal weight in the middle location in controls (0.061g  0.001 vs. 0.055g  0.002), GD 4 (0.033g  0.003 vs. 0.049g  0.004), and GD 17 (0.047g  0.002 vs. 0.038g  0.002) exposed animals was identified. Additionally, GD 4 exposure produced significantly smaller feti in the right uterine horn at the ovarian end (0.052g  0.003 vs. 0.029g  0.003) and middle of the right uterine horn (0.060g  0.001 vs. 0.033g  0.003). GD 17 exposure produced significantly smaller feti in the left uterine horn middle location (0.055g  0.002 vs. 0.033  0.002). Placental weights were unaffected, and placental efficiency was reduced in the right uterine horn middle location after GD 17 exposure (5.74g  0.16 vs. 5.09g  0.14). These findings identified: 1) differences in fetal weight of controls between the right and left horns in the middle position, and 2) differential effects of single whole-body pulmonary exposure to titanium dioxide nanoparticles on fetal weight by position and window of maternal exposure. In conclusion, these results indicate that consideration for intrauterine position, maternal weight, and number of feti per horn provides a more sensitive assessment of FGR from rodent reproductive and developmental studies.